Pengaruh Rasio Keuangan pada Financial Distress - Mahaningrum, A. A. Istri Agung; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi, 2020)
The purpose of this study is to obtain empirical evidence about the effect of financial ratios on financial distress. This research was conducted on companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange in the 2016-2018 period. The sample was determined using the nonprobability sampling method with a purposive sampling technique. The number of samples used was 39 companies and the overall observation data for the 2016-2018 period was 117 observation data. The analysis technique used is logistic regression analysis. Based on the results of the study, it was stated that liquidity ratios had no effect on financial distress, leverage ratios had a positive effect on financial distress, profitability ratios had a negative effect on financial distress, activity ratios had no effect on financial distress and growth ratios had no effect on financial distress. Keywords: Financial Distress; Financial Ratios; Logistic Regression.